Kerajaan Safawi di Persia: Pembentukan, Kemajuan, dan Kemunduran - Abu Bakar Mustafa; Ansar Tohe (Al-Kindi, 2026)
This study aims to analyze the establishment, development, golden age, decline, and collapse of the Safavid Dynasty, as well as its influence on the development of Islamic politics and the geopolitical dynamics of the Middle East. The research employed a qualitative approach using library research with historical and Islamic political perspectives. Data were collected through documentation of books, scientific journals, historical records, and other relevant academic sources, then analyzed using descriptive-analytical techniques involving data reduction, interpretation, and conclusion drawing. The findings reveal that the Safavid Dynasty successfully reunited Persia after prolonged political fragmentation and transformed its religious identity by establishing Twelver Shi'ism as the official state doctrine. Under Shah Abbas I, the dynasty reached its peak through military, administrative, economic, cultural, and scientific reforms. However, weak leadership, internal conflicts, economic decline, military deterioration, corruption, and external invasions led to its collapse. Despite its political downfall, the Safavid legacy continues to shape Iran's national identity and significantly influences contemporary Islamic politics, particularly Sunni-Shi'a relations and the geopolitical landscape of the Middle East.